Hydraulic characteristics of a fractured crystalline basement aquifer in Nzhelele area, Limpopo Province, South Africa. Issue 1 (1st January 2021) - Makungo, R.; Odiyo, J.O.; Ndiritu, J.G.
Abstract: Knowledge on hydraulic characteristics of fractured crystalline basement aquifers is limited resulting to lack of reliable information for effective groundwater management. This is crucial as these aquifers provide good sources of potable water in most rural communities. Heterogeneous nature of these aquifers requires detailed understanding and accurate estimation of hydraulic characteristics. This study estimated hydraulic characteristics of a fractured crystalline basement aquifer and inferred their influence on groundwater storage potential and flow. Aquifer Test Solver was used for automatic curve matching to identify appropriate aquifer models and test solutions for estimating hydraulic characteristics. Root-mean-square error (RMSE), mean absolute error (MAE) and correlation coefficient (R) were used to evaluate the performance of the fitted models. Plotted derivative curves were used to identify the presence of fracture dewatering in the aquifer. The R, RMSE and MAE ranged from 0.702 to 0.995, 0.31–3.45 m and 0.23 to 3.06 m, respectively. The fits between measured and estimated drawdowns were good and performance mostly acceptable and comparable to those of related studies. Storativity, transmissivity and hydraulic conductivity ranged from 0.0003 to 0.0680, 0.78 to 12.3 m 2 /day and 8.56 × 10 −7 to 5.32 × 10 −6 m/s, respectively. The storage potential of the aquifer varied from low to high, ability to transmit water per unit area was mostly medium though the ability to transmit water through its entire thickness was mostly low. The study area is dominated by leaky aquifer and fracture dewatering. Groundwater use should be monitored and managed effectively to avoid fracture dewatering and its associated risks.